2013
DOI: 10.11604/pamj.2013.14.14.1906
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral resection of prostate syndrome: report of a case

Abstract: We report a case of transurethral resection of prostate (TURP) syndrome. A 78-year-old man with prostatic hypertrophy was scheduled for transurethral resection of the prostate under spinal anesthesia. 30 minutes after the end of the surgery, the patient presented signs of TURP syndrome with bradycardia, arterial hypotension, cyanosis, hypoxemia and coma. The electrolytes analysis revealed an acute hyponatremia (sodium concentration 125 mmol/L). Medical treatment consisted of hypertonic saline solution 3%, volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…In our studies, examining MetS and hypertension among African American women, we found that both systolic and diastolic blood pressure were associated with waist circumference, but not BMI and % body weight [ 51 ]. Thus, the conventional notion that insulin resistance is pivotal for CVD and hypertensive events does not appear to be supported in African American women, consistent with several previous reports in insulin resistant, nondiabetic, obese African Americans [ 20 , 21 , 25 ] and Black South African women [ 23 , 31 , 34 , 39 , 40 ], and native Ghanaians [ 4 , 24 ] in contrast with those of white women. High blood pressure or its surrogate e.g., chronic kidney disease, microalbuminuria are more prevalent in black PAA than whites.…”
Section: Criteria Of Metabolic Syndrome Using the National Cholestsupporting
confidence: 84%
See 2 more Smart Citations
“…In our studies, examining MetS and hypertension among African American women, we found that both systolic and diastolic blood pressure were associated with waist circumference, but not BMI and % body weight [ 51 ]. Thus, the conventional notion that insulin resistance is pivotal for CVD and hypertensive events does not appear to be supported in African American women, consistent with several previous reports in insulin resistant, nondiabetic, obese African Americans [ 20 , 21 , 25 ] and Black South African women [ 23 , 31 , 34 , 39 , 40 ], and native Ghanaians [ 4 , 24 ] in contrast with those of white women. High blood pressure or its surrogate e.g., chronic kidney disease, microalbuminuria are more prevalent in black PAA than whites.…”
Section: Criteria Of Metabolic Syndrome Using the National Cholestsupporting
confidence: 84%
“…Other studies in SSA found higher prevalence rates of MetS. For example, Katchunga et al [ 31 ] found the MetS prevalence to be 43.6% among Congolense with at least one major cardiovascular risk factor. Note however, that in this study, the subjects were recruited based on having one prior CVD factor.…”
Section: Criteria Of Metabolic Syndrome Using the National Cholestmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this procedure potentially leads to a complication known as TURP syndrome (Hahn et al, 2000). Transurethral resection of prostate syndrome is clearly defined as excessive irrigation fluid absorption leading to hyponatremia and hypervolemia (Gupta et al, 2010;Demirel et al, 2012;Boukatta et al, 2013). This syndrome is characterized by mental confusion, nausea and vomiting, hypertension, bradycardia and visual impairment.…”
Section: Introductionmentioning
confidence: 99%
“…In 1956, the clinical picture was summarized as “dilutional hyponatremic shock,” due to the severe arterial hypotension and even cardiovascular collapse that occurs postoperatively 4-7. Although the incidence of this syndrome is decreasing, complete or incomplete forms of TUR syndrome occur in up to 5% percent of patients in some case series of TURPs performed with monopolar electrocautery 8-10.…”
Section: Introductionmentioning
confidence: 99%